Analysis of the ETIS system of indicators for the assessment and monitoring of tourism sustainability in the city of Split, Croatia - Pavlinović Mršić, Slađana; Čale, Dubravka (Oeconomica Jadertina, 2020)
ETIS is a tool that serves to improve the sustainability of the tourist destination, and the purpose of this research is to contribute to the application of this tool in the city of Split. The aim of the research was to determine the current situation and the possibilities of improvement by application of ETIS in Split. It was determined what data the City of Split is currently available for each indicator, and what additional existing data should be collected from other sources. Indicators that are not covered by the existing data need to be monitored by conducting survey questionnaires available in the ETIS toolkit. The analysis showed that the Environmental Impact indicators are the least covered by the existing data and it is primarily recommended to make an effort in collecting data within this group of indicators.